Integration of Local Wisdom in E-Modules of PjBL Model: Facilitating Understanding Concept and Learning Independence of High School Physics Students - Sukma, Melani Dyah Ayu; Yusman Wiyatmo; Kuncoro Asih Nugroho; Bayu Setiaji (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to determine the level of feasibility and effectiveness of the e-module PjBL model that integrates Local Wisdom. The type of research conducted is development research with the 4D model, which includes Define, Design, Develop, and Disseminate.. The samples used were 36 students for limited testing and 3 MIPA XI classes consisting of 108 students for field testing which were divided into experimental classes, control class 1, and control class 2. The instruments used included e-modules, lesson plans, pretest-posttest questions, learning independence questionnaires and student response questionnaires. The data obtained were analyzed using inferential statistical analysis and descriptive analysis. Based on the analysis of validation of experts, practitioners and student response questionnaires, the results showed that the developed e-modules were feasible to use in improving concept understanding and learning independence. Based on the field test, the developed e-module is effective to be used in improving students' concept understanding and learning independence.